PENGARUH PEMBIAYAAN PERBANKAN DI SEKTOR LISTRIK, AIR DAN GAS TERHADAP PERTUMBUHAN SEKTOR LISTRIK, AIR DAN GAS DI KALIMANTAN BARAT - Lutfi B01109107, Akhmad Faisal (Jurnal Pembangunan dan Pemerataan, 2015)
The research aimed to know the growth of bank financing in electricity, water and gas sectors on the growth of these sectors, and to know the influence of financing: Bank Pemerintah Daerah (X1) on growth electricity, water and gas sectors, Bank Swasta Nasional (X2) on development of electricity, water and gas sectors. The research used descriptive-quantitative analysis method. The research used secondary data of time series (in quarter) from 2007 to 2013, which was gathered from Bank Indonesia and Central Bureau of Statistics and other sources. The research finding shows that the growth of Bank Pemerintah Daerah financing (X1) and Bank Swasta Nasional (X2) had an unidirectional relationship on the growth of bank financing in electricity, water and gas sectors and represented that credits in Bank Pemerintah Daerah (X1) and Bank Swasta Nasional (X2) had positive impact.This result was based the research regression showing that the two banks had positive impacts and had influenced the growth of electricity, water and gas sectors by 77% and 23 % in other sectors. This result was in line with the research hypothesis.Â  Key words: Banking Financing, Growth of PDRB in Electricity, Water and Gas Sectors